Effectiveness of breadfruit leaf extract in mouthwash formula to inhibit the bacteria of Streptococcus mutans that causes caries - Khairi, Nur; Aisyah, Andi Nur; Indrisari, Maulita; Sukmawati, Sukmawati; Nisa, Michrun (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Dental caries is caused by Streptococcus mutans, which forms biofilms and produces acid that damages tooth enamel. Prevention is often achieved through mouthwashes containing antibacterial agents, but commercial products may have side effects due to chemical ingredients. Artocarpus altilis (breadfruit) leaves contain bioactive compounds like flavonoids and tannins, which have potential as natural antibacterial agents. Objective: This study aimed to evaluate the antibacterial activity of Artocarpus altilis leaf extract and formulate an effective mouthwash against Streptococcus mutans. Methods: The study used a true experimental design with a pretest-posttest control group. The extract was obtained by maceration with 96% ethanol. Three mouthwash formulations were prepared with varying glycerin concentrations (15%, 20%, and 25%). Antibacterial activity was assessed using the paper disk method, and data were analyzed using Kruskal-Wallis and Mann-Whitney tests. Results: The 2-4% extract had strong antibacterial activity, with inhibition zones ranging from 20.25–23.81 mm, significantly different from the negative control (p<0.05). The mouthwash formulations were liquid, yellow-green in color, with a characteristic breadfruit and mint scent, pH ranging from 5.5 to 7.9, and viscosity of 1 cPs. The mouthwash exhibited strong antibacterial activity, with inhibition zones between 18.81±1.5 mm and 18.94±0.5 mm, showing no significant differences across formulas (p>0.05). Conclusion: The 2% Artocarpus altilis extract and 15% glycerin formula was stable and effectively inhibited Streptococcus mutans